Desertification Assessment Using the Modified Mediterranean Desertification and Land Use Model in a Karst Plateau - Umberto Samuele D’Ettorre; Isabella Serena Liso; Vincenzo Parisi; Mario Parise (Geosciences, 2024)
Desertification is among the most severe environmental problems in many countries at present, and threatens the integrity of natural environments and the sustainability of related natural resources. This work aims to assess proneness to desertification in the Alta Murgia karst plateau (Apulia, Southern Italy) through the integration of the modified Mediterranean Desertification and Land Use model (MEDALUS) with a GIS-based approach. The model includes indexes for climate, vegetation, soil, and management, all combined to assess environmentally sensitive areas (ESAs) regarding desertification. Given the karst features of the study area, the management index was modified and renamed the Karst Management Quality Index (KMQI). This modification was made by incorporating the Karst Disturbance Index (KDI), based on a series of indicators divided into five categories: geomorphology, hydrology, atmosphere, biota, and cultural factors. According to the model, the results indicated that the whole area (97%) is within the Critical type of ESA, with no area being assessed as the “Non-Affected” or “Potential” type. A total of 57% of the study area falls into Critical sub-type 2, 32% falls into sub-type 3, and 8% falls into sub-type 1. The remaining percentage (3%) belong to a non-optimal category, i.e., the Fragile type (sub-type F3) class. The obtained results could be explained, more than by climatic or ecological factors, by a series of anthropogenic activities carried out over the years that strongly modified and disturbed the original karst landscape, with a highly negative impact on the Alta Murgia karst.